Finite element analysis for multi-leaf structures with frictional contact and large deformation - Chen, Xian; Nakamura, Kazuhiro; Mori, Masahiko; Hisada, Toshiaki (Computer Assisted Methods in Engineering and Science, 2000)
The analysis of multi-leaf structures should be performed taking friction into account. The objectivity of friction law should be preserved because large deformation generally occurs. By use of the convected coordinate system, the objectivity can be preserved naturally. Therefore, in finite element analysis, the element local coordinate system can be used. However, when a contact point slides over the element boundary, a problem arises due to the discontinuity of the local coordinates between elements. In this work, an algorithm is proposed, i.e., the formulation is essentially based on the convected coordinate system while the sliding term is redefined as a spatial vector and is calculated in the reference configuration. Thus, the finite sliding due to large deformation can be treated without paying special attention to the limit of the local coordinate system. Two numerical examples including a simplified model of a leaf spring structure used in nuclear power plants are given.